The Effect Of Work Performance, Work Stress And Work Load On Job Satisfaction At Class II A Corrective Institution In Binjai - Angelia Hosiana Lumbantoruan; M. Chaerul Rizky (UNIVED Press, 2026)
This study aims to determine the effect of work performance, work stress, and workload on job satisfaction at Class II A Binjai Penitentiary. This type of research is associative research with a quantitative approach, using a questionnaire as a data collection tool. The sample in this study consisted of 60 respondents, which were determined using the slovin calculation. For data analysis, multiple linear regression was used with the help of SPSS version 23 software. The results of the study indicate that partially, work performance has a significant positive effect on job satisfaction, while work stress and workload have no effect. Simultaneously, work performance, work stress, and workload have a positive and significant effect on job satisfaction of employees at Class II A Binjai Penitentiary. This research model is able to explain 55.6% of the variation in job satisfaction.